Engineering cAMP Receptor Protein (CRP) for improved cell phenotypes during fermentation - Chong, Hui Qing (2013)
Microorganisms are widely used in industries for various industrial applications, such as the production of commodity chemicals, biofuels, and recombinant proteins. However, a major limitation in using these microorganisms is their low tolerance towards various stresses during fermentation. Classical strain engineering approaches (UV/chemical mutagenesis, adaptive evolution and metabolic engineering) have been utilized to improve strain phenotypes valuable in industry, but are usually resource-intensive and only marginally efficient. Transcriptional engineering approach has gained much attention in strain engineering in recent years, which can greatly shorten variant selection period from months to just several days. In this work, error-prone PCR technique was adopted to engineer global transcription factor cAMP receptor protein (CRP) in Escherichia coli, to generate genetic and thus phenotypic diversity and obtain mutants with desired phenotypes, including ethanol and acetate tolerance. Random mutagenesis libraries of CRP mutants were created and transformed into E. coli Δcrp microbial host. Cells were cultured under different stress, namely ethanol or acetate, and “winners” were selected based on growth. The best mutant under each stress condition was further characterized according to its cross-tolerance, changes in transcript profile and cell morphology. For instance, three E. coli mutants (E1-E3) with elevated ethanol tolerance were selected, and the best ethanol-tolerant strain E2 had single amino acid substitution M59T, which was then integrated into the genome to create iE2. When exposed to 150 g/L ethanol, the survival rate of iE2 after 15 min was about 12 %, while that of parent strain was < 0.01 %. Real-time PCR analysis on CRP-regulated genes revealed that several genes involved in enterobactin biosynthesis (entH, entD) and iron ion transport ( fecA, fecB), and general stress response (osmY, rpoS) were differentially expressed in iE2. Four mutants (A1-A4) with improved acetate tolerance were also identified, with A2 (D138Y) having the highest growth rate. Real-time PCR analysis using OpenArray® revealed that CRP-regulated genes, especially those involved in the uptake and utilisation of sugars, amino sugars and amino acids, were differentially expressed between A2 and WT.